Malay cuisine cooking recipe recommendation system using Genetic Algorithm (GA) / Nur Nazihah Ismail - Ismail, Nur Nazihah (Faculty of Computer and Mathematical Sciences, 2017)
Malaysia is popular with various types of dishes. There are a lot of dishes such as Malays, Chinese and Indian cuisines. Recipe is one of important medium in order to make the dishes. Nowadays, people are referring recipes on website, Facebook or asking other people. However, there are a few problems exists by using current system such as it is does not match with the available ingredients that user have. People need suggestion to help them in order to find recipes that suits with their preferences. Hence, recommendation system for food recipes preparation has been proposed to help people to find recipes. This recommendation system will help people by suggesting recipes that follow user preferences. Besides, there are various techniques that able to be implemented in recommendation system. For this recommendation system, Genetic Algorithm (GA) is used as a technique to find the optimal results. GA is an evolutionary technique. In addition, GA able to handle multiple solution searches and solve problems, more straightforward and more flexible because it is easier to transferred in any platform. This system met all of the objectives which are successfully recommends recipe based on ingredients, equipment and time for cooking. Besides, this system also successfully developed by using Genetic Algorithm technique and lastly, all the system function well. As a result, this system suggests recipes that match with user preferences since there are too many criterions that need to match with user wants. Lastly, this algorithm obtains convergence result and met the optimal solution.